2016
DOI: 10.1021/acs.inorgchem.6b00032
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthetic Route for the Preparation of an Amorphous Co/Fe Prussian Blue Coordination Compound with High Electrocatalytic Water Oxidation Activity

Abstract: Co/Fe Prussian Blue coordination networks have recently been investigated for heterogeneous water oxidation catalysis. Despite their robustness and stability in both acidic and neutral media, the relatively low current density obtained is their main drawback as a result of their low surface concentration. A novel synthetic approach was employed using a pentacyanometalate-based metallopolymer for the preparation of amorphous Co/Fe coordination polymers to overcome this problem. The surface concentration was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 46 publications
5
100
0
Order By: Relevance
“…This changew as also confirmed by XRD results, in which the diffraction angle (2q)o ft he (121)p lane for Co 3 (BO 3 ) 2 @CNT shifts slightly to higher angles compared with Co 3 (BO 3 ) 2 as ar esult of the decrease in interplanary distance between (121) planes. [38] B1s ( Figure 3b)a nd O1s ( Figure 3c)s ignals are observed at approximately 192 and 533 eV,r espectively,f or Co 3 (BO 3 ) 2 .Amild shift toward slightly higher binding energies is observed in Co 3 (BO 3 ) 2 @CNT,w hich can be attributedt ot he influence of the electron densities of the carbon atoms from the CNTst o Co 3 (BO 3 ) 2 . Figure 3s hows the resultso fX PS analysis of Co 3 (BO 3 ) 2 and Co 3 (BO 3 ) 2 @CNT samples.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This changew as also confirmed by XRD results, in which the diffraction angle (2q)o ft he (121)p lane for Co 3 (BO 3 ) 2 @CNT shifts slightly to higher angles compared with Co 3 (BO 3 ) 2 as ar esult of the decrease in interplanary distance between (121) planes. [38] B1s ( Figure 3b)a nd O1s ( Figure 3c)s ignals are observed at approximately 192 and 533 eV,r espectively,f or Co 3 (BO 3 ) 2 .Amild shift toward slightly higher binding energies is observed in Co 3 (BO 3 ) 2 @CNT,w hich can be attributedt ot he influence of the electron densities of the carbon atoms from the CNTst o Co 3 (BO 3 ) 2 . Figure 3s hows the resultso fX PS analysis of Co 3 (BO 3 ) 2 and Co 3 (BO 3 ) 2 @CNT samples.…”
Section: Resultsmentioning
confidence: 89%
“…The CV of Co 3 (BO 3 ) 2 displays aq uasireversible redox couple with an oxidation peak at around1 .10 Va nd ar educ-tion peak at 1.00 Vv ersus the NHE reference electrode (E 1/2 = 1.05 V, E c ÀE a = 100 mV), whichc an be assigned to the Co 2 + /Co 3 + redox couple. An improvement in the onset overpotentialw as also observed with Co 3 (BO 3 ) 2 @CNT compared with Co 3 (BO 3 ) 2 .A no nset overpotential of 206 mV is recorded, which is one of the lowesto verpotentials achieved among cobalt-based catalyst films includingC oPi (h:2 80 mV), [4] Co(PO 3 ) 2 (h:3 10 mV), [41] CoNCN( h:3 20 mV), [42] CoFe(CN) 5 -PVP (h:3 60 mV), [38] Co 3 O 4 (h:4 34 mV), [43] and Co-Bi NS/G (h: 235 mV). [39,40] As imilarp rofile was observed for Co 3 (BO 3 ) 2 @CNT.T he comparison of CVs of Co 3 (BO 3 ) 2 @CNT, Analysis of Tafel plots shows that the slope (67 mV dec À1 )f or Co 3 (BO 3 ) 2 @CNT is slightly lower than that obtained for Co 3 (BO 3 ) 2 (84 mV dec À1 ), mainly owing to the conductive behavioro fC NTs ( Figure 4b).…”
Section: Resultsmentioning
confidence: 96%
“…[21] Different perspectives of cobalt-based Prussian blue analogues (PBAs) as WOCs have recently been explored by us and other researchers. [25] Thea forementioned study and many others reveal that the ammonia group of [Fe(CN) 5 (NH 3 )] 3À complex can be substituted with pyridyl containing organic moieties via astraightforward synthesis. [32] Recently,w ee mployed ap entacyanoferrate complex rather than ah exacyanometal precursor to prepare an amorphous PBAw ith enhanced electrocatalytic activity.…”
mentioning
confidence: 96%
“…[10][11][12][13][14][15][16][17][18][19] Although the use of robust heterogeneous assemblies such as oxides could be apromising solution to improve stability,the lack of complete control on the coordination of metal ions in oxide chemistry does not allow the preparation of oxidebased dyads. [22][23][24][25][26][27][28][29][30][31] PBAs consist of earth-abundant elements,perform at relatively low overpotentials (< 500 mV for ac urrent density of 1mAcm À2 ), exhibit exceptional stabilities in awide pH range (from 1to13), and can operate even with molecular chromophores for light-driven catalysis. [21] Different perspectives of cobalt-based Prussian blue analogues (PBAs) as WOCs have recently been explored by us and other researchers.…”
mentioning
confidence: 99%
“…It is suggested that the C‐coordinated metal ions can affect the electron density near the N‐coordinated metal ions and introduce defects that can provide binding sites for water molecules near the active site. Aksoy et al found that PBAs and polymers can be hybridized to improve their catalytic activity by inducing the formation of amorphous, defect‐rich PBAs . Han et al reported that chemical etching of PBAs also improves their catalytic performance, but its underlying principle is still unclear .…”
Section: Self‐assembly and Surface Precipitation Of Precursors Formentioning
confidence: 99%